ALLERGIC PROCTOCOLITIS IN INFANTS: analysis of the evolution of the nutritional status - CAMARGO,Ludmilla S (2016)
ABSTRACT Background Allergic proctocolitis is a disease that affects infants in the first months. The change in feed is the primary factor for clinical improvement and maintenance of the nutritional status of the infant. Objective Study the anthropometric evolution of infants with allergic proctocolitis at diagnosis and 1 to 6 months after nutritional intervention. Methods A retrospective cohort of infants with allergic proctocolitis diagnosis followed at the Pediatric Gastroenterology Institute of São Paulo (IGASTROPED), Brazil. The database with clinical, therapeutic and anthropometric data was obtained from medical records of outpatient infants. The therapeutic intervention was characterized by 1) exclusive breastfeeding with maternal exclusion diet of the six allergens (EBF-MED) or 2) no breastfeeding and use of hypoallergenic formulas. Results Of the 44 infants diagnosed with allergic proctocolitis, 23 were female. The median age of the infants was 3.5 months at the time of admission and 6 months after the intervention. The main clinical complaint was hematochezia with or without other symptoms of allergic proctocolitis. No difference was shown in the infants anthropometric evaluation between the two diets. Conclusion The duration of the allergic proctocolitis did not induce worsening of the infants nutritional status. Importantly, both nutritional interventions were able to keep the infants within the growth channel and resulted in the total clinical symptoms remission. Considering the fundamental mother-child link promoted by breastfeeding, the present data highlights the beneficial role of EBF-MED on the nutritional status of infants diagnosed with allergic proctocolitis in addition to the lower cost that breastfeeding brings compared the use of hypoallergenic formulas.